(untitled) (Journal of the College of Basic Education, 2022)
The aim of the current research is to: "Knowing the structure of the students of the Mathematics Department in the faculties of Basic Education, and to achieve this goal, the following questions must be answered: 1) What is the mathematical structure of the students of the mathematics department in the faculties of basic education? 2) What is the significance of the statistical difference in the mathematical structure of the sample members according to the gender variable (male-female)? The current research was conducted on students of the Department of Mathematics in the faculties of basic education in Iraqi universities, (morning study), the fourth stage, and for both sexes (males and females), and (300) male and female students were selected, by the random stratified method, and to answer the above questions, the researcher prepared A test to measure the mathematical evidence of the sample members. The test consisted of (40) items in its final form. The researcher extracted for this test two indicators of validity: First: the apparent validity, by presenting the test items to a group of experts. One of the paragraphs with the total test score, and the correlation coefficient of each paragraph was found with the field to which it belongs. The researcher also made sure of the stability of the test using the method of internal consistency coefficient (Alpha - Cronbach), and the reliability coefficient reached (0.832), and after applying the search tool to the sample, The test has been corrected and sorted The data and its statistical analysis, where the results of the research showed that: 1- The sample members have a mathematical structure. 2- The members of the research sample (male-female) have the same level in the mathematical structure. In light of these results, the researcher reached a number of conclusions, recommendations and suggestions. The most important conclusions: 1) Students of the Mathematics Department in the faculties of Basic Education in general (male-female) possess the mathematical structure. 2) There is no statistically significant difference between males and females. The most important recommendations: 1) Including topics that clarify the mathematical structure in the curricula established in the mathematics departments in educational faculties, especially the faculties of basic education. 2) Developing the process of building mathematics curricula in the light of the components of the mathematical structure for the different school stages. The most important suggestions: Conducting some studies to find out the mathematical structure of students of faculties of education, students of faculties of science, mathematics teachers at the secondary level, or mathematics teachers at the elementary level.